Studi Perbandingan Penurunan dan Tegangan Tanah di Bawah Fondasi Lentur Menggunakan Metode Empiris dan Elemen Hingga - Hosiana, Nikita; Chrismaningwang, Galuh; Surjandari, Niken Silmi; Dananjaya, Raden Harya (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
Safe infrastructure development requires a strong foundation to distribute the building load to the ground below. The study of soil behavior under load is very important in geotechnical engineering. This research aims to compare soil stress calculations using the Boussinesq and UNStrain theories and compare the settlement values at foundation corners in the immediate settlement calculations using the Steinbrenner and UNStrain methods. UNStrain is an application that uses the finite element method to calculate soil deformation and stress. However, it still requires validation because this program is still in the development stage and requires testing for accuracy. The accuracy of UNStrain application calculations was validated using empirical methods by comparing soil stress values with the Boussinesq theory. The research was carried out in the case of a flexible foundation with an evenly distributed load in longitudinal strips of 90 kN/m on sandy soil. RMSE shows a value of 2.90 kN/m² for vertical stress and 2.64 kN/m² for horizontal stress, while MAPE for vertical stress is 2.94% and horizontal stress is 5.79%, which shows that it is accurate in comparison to UNStrain soil stress calculations towards Boussinesq's theory. Calculation of the settlement at the corner of the foundation with the immediate Steinbrenner settlement produces a value of 0.40 cm and UNStrain produces a value of 0.79 cm.